2012
DOI: 10.1038/nrurol.2012.234
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone treatment in normogonadotropic infertile men

Abstract: Several empirical treatments have been proposed to treat idiopathic infertility in men, including follicle-stimulating hormone (FSH). FSH administration is effective in patients with hypogonadotropic hypogonadism, which suggests it might be useful in patients with oligozoospermia who have normal FSH levels. Indeed, many studies have evaluated the efficacy of FSH administration in these patients, several of which have shown improvements in sperm parameters. By contrast, other studies have not reported any signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…Other studies have examined the quality of conventional sperm parameters after pharmacological treatment with FSH in patients with idiopathic infertility, with discordant results [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the quality of conventional sperm parameters after pharmacological treatment with FSH in patients with idiopathic infertility, with discordant results [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of the results of FSH therapy have been achieved with men who have oligoasthenozoospermia (OAT) not NOA. Nonetheless, the efficacy of FSH therapy for treatment of OAT remains controversial [55][56][57]. Several studies have evaluated the efficacy of FSH administration for men with OAT with resultant improvements in sperm parameters, whereas other studies have not shown any significant effect.…”
Section: Fsh Therapy For Spermatogenic Disordersmentioning
confidence: 99%
“…Several studies have evaluated the efficacy of FSH administration for men with OAT with resultant improvements in sperm parameters, whereas other studies have not shown any significant effect. There are several opinions regarding who would benefit from FSH treatment: 1) oligozoospermic men with normal serum FSH levels [57], and 2) FSH receptor genotype men with at least one serine in position 680 who had a significant increase in sperm parameters [58]. Most important, the influence of technology for female infertility treatment such as ICSI complicates the results of male infertility treatment (effect-modifying factor) [55].…”
Section: Fsh Therapy For Spermatogenic Disordersmentioning
confidence: 99%
“…The potential value of LH secretion is an indicator of sperm quality in adult bulls after the administration of GnRH; four SNPs of the LH gene in water buffaloes are associated with sperm quality traits (Cheng et al, ). Contributed to spermatogenesis, FSH is empirically used to treat male idiopathic infertility; FSH treatment could improve both quantitative and qualitative sperm parameters by acting on sperm maturation, thereby increasing the proportion of functionally competent cells (Casamonti et al, ; Valenti et al, ). More directly, many studies demonstrated that the humoral cascade effect of GnRH determines testicular development, maturation and function activity.…”
Section: Introductionmentioning
confidence: 99%